Perovskite photovoltaic cell packaging adhesive film

Through the high grafting rate and low free content melt grafting technology of silane coupling agent grafting polyolefin elastomer, combined with other additives, the polarity incompatibility and insufficient peel strength of perovskite photovoltaic cell packaging film is solved. Problem, a packaging adhesive film with high bonding strength and anti-aging properties is achieved, avoiding slippage and meeting the packaging needs of perovskite photovoltaic cells.

CN119193012APending Publication Date: 2024-12-27AORUIBANG (XIAMEN) NEW MATERIAL CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411301056.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing perovskite photovoltaic cell packaging film has problems with precipitation and peel strength attenuation caused by incompatibility of polar additives and polyolefin elastomers, and has slippage, and is sensitive to organic residues and water vapor, making it difficult to meet high bonding. Requirements for strength and anti-aging properties.

Method used

The polyolefin elastomer is grafted by silane coupling agent. Through the melt grafting technology with high grafting rate and low free silane coupling agent content, a packaging film with high polarity and high bond strength is formed, combined with a crosslinking agent, Crosslinking agent, antioxidant and light stabilizer improve the anti-slip and aging resistance of the adhesive film.

Benefits of technology

The packaging film with high bonding strength and anti-aging properties is achieved, which avoids slippage and maintains a high bonding strength after aging for a long time, meeting the packaging needs of perovskite photovoltaic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193012A_ABST
    Figure CN119193012A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite photovoltaic cell packaging adhesive film, and relates to the technical field of solar cell adhesives. The perovskite photovoltaic cell packaging adhesive film comprises the following raw material components: a silane coupling agent grafted polyolefin elastomer; the grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not lower than 3wt%, and the weight content of the free silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not higher than 0.2 wt%. Preferably, the silane coupling agent grafted polyolefin elastomer is obtained by adopting a melt grafting method. The packaging adhesive film disclosed by the invention is high in bonding strength, good in ageing resistance and relatively good in skid resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cell adhesives and relates to a perovskite photovoltaic cell encapsulation adhesive film. Background Art

[0002] Photovoltaic encapsulation film is used to achieve firm encapsulation protection and long-term outdoor weather resistance for photovoltaic cells. Perovskite photovoltaic cells are photovoltaic cells with very good application prospects. Polyolefin elastomer is the main material of commonly used photovoltaic encapsulation film, which is usually used in combination with some additives or modified. However, the polarity of the additive is generally high, and the polarity of the polyolefin elastomer is low. The additive may be incompatible with the polyolefin elastomer, resulting in precipitation and migration to the surface of the film, or the peel strength of the film may decay after aging. These various reasons lead to the slippage of the encapsulation film, which is not conducive to the stable encapsulation effect of the encapsulation film. In order to solve the slippage problem of the encapsulation film, the prior art discloses some methods, such as using a polymerizable monomer with an ether bond of one or more repeating units as an anti-PID monomer to achieve the modification of the polyolefin elastomer E by melt grafting onto the polyolefin elastomer, thereby improving the compatibility with the additive. This technology still has the following shortcomings: (1) the reaction of the anti-PID monomer is incomplete, and the residual anti-PID monomer will still cause slippage after subsequent precipitation; (2) the peel strength between the modified POE and the photovoltaic cell substrate is not enough, which is prone to slippage, or it is prone to slippage after aging.

[0003] Perovskite photovoltaic cells have higher requirements for encapsulation films and are more sensitive to organic residues and water vapor. They require low organic residues, high bonding strength, and good anti-aging performance in the encapsulation films. Therefore, it is necessary to further study the modification of photovoltaic encapsulation films, especially perovskite photovoltaic cell encapsulation films. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a perovskite photovoltaic cell encapsulation film.

[0005] The technical solution of the present invention is as follows:

[0006] A perovskite photovoltaic cell encapsulation adhesive film, the raw material components of which include a silane coupling agent grafted polyolefin elastomer;

[0007] The grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not less than 3wt%, and the weight content of the free silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not higher than 0.2wt%.

[0008] Preferably, the weight proportion of the silane coupling agent grafted polyolefin elastomer in the packaging film is not less than 90%.

[0009] Preferably, the silane coupling agent is a silane coupling agent having a carbon-carbon double bond at the end group.

[0010] More preferably, the general formula of the silane coupling agent is as shown in the following formula (1):

[0011] CH2=C(R 1 )R 2 S i 3 a (OR 4 ) b (1)

[0012] Among them, R 1 is selected from H or C1-C4 alkyl, R 2 is absent, C1-C8 alkylene or C2-C10 substituted alkylene, R 3 and R 4 Independently selected from C1-C4 alkyl, 0≤a≤1, a+b=3.

[0013] Preferably, the grafting rate of the silane coupling agent in the silane coupling agent-grafted polyolefin elastomer is not less than 4 wt %.

[0014] Preferably, the grafting rate of the silane coupling agent in the silane coupling agent-grafted polyolefin elastomer is not higher than 10 wt %.

[0015] More preferably, the grafting rate of the silane coupling agent in the silane coupling agent-grafted polyolefin elastomer is not higher than 8 wt %.

[0016] Preferably, the silane coupling agent grafted polyolefin elastomer is prepared by a melt grafting method.

[0017] More preferably, the melt grafting is carried out using a screw extruder with a melting section temperature of 80-200°C and a die temperature of 150-200°C.

[0018] Preferably, the raw material components further include one or a combination of two or more of a cross-linking agent, a co-cross-linking agent, an antioxidant, a light stabilizer and an ultraviolet absorber.

[0019] The beneficial effects of the present invention are:

[0020] (1) The grafting rate of the silane coupling agent in the grafted polyolefin elastomer of the present invention is relatively high, and the high content of the silane coupling agent provides higher polarity and bonding strength, and can have better compatibility with the auxiliary agent. At the same time, the high bonding strength formed by chemical bonding has good anti-aging effect. Therefore, the encapsulation film of the present invention has good anti-slip effect.

[0021] (2) The present invention adopts a melt grafting method, and the added silane coupling agent with a relatively high amount of end groups containing carbon-carbon double bonds can basically undergo a melt grafting reaction completely. The added silane coupling agent is basically grafted onto the polyolefin elastomer, and the silane coupling agent basically does not remain. Avoiding the silane coupling agent residue can further improve the anti-skid performance.

[0022] (3) The packaging film of the present invention is modified by melt grafting, which combines the factors of low monomer residue, high polarity of modified polyolefin elastomer, high bonding strength and good anti-aging effect, so that the packaging film has good anti-slip performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a comparison of the infrared absorbance spectra of the film before and after detection in the test method of the free silane coupling agent in Example 1. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0025] In order to improve the bonding strength of the encapsulation film and have good aging resistance, high conversion rate of the modified monomer and substantially no residue, and improve the anti-slip performance of the encapsulation film, the present invention provides a perovskite photovoltaic cell encapsulation film, the raw material components comprising a silane coupling agent grafted polyolefin elastomer;

[0026] The grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not less than 3wt%, and the weight content of the free silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not higher than 0.2wt%.

[0027] Polyolefin elastomer refers to copolymers of ethylene or propylene with 1-butene, 1-octene, 1-hexene, etc., and the more common ones are ethylene / 1-octene copolymer (POE) and propylene / 1-octene copolymer (POP), which have the characteristics of good weather resistance, high barrier properties, good anti-PID performance, etc., but also have the disadvantages of low polarity, poor compatibility with additives, low bonding strength, etc. In the packaging film of the present invention, the main material is a polyolefin elastomer grafted with a silane coupling agent, and the silane coupling agent not only greatly improves the polarity of the packaging film, but also can achieve good bonding strength and anti-aging performance with the substrate due to the high grafting rate of the silane coupling agent, and the weight content of the free silane coupling agent is very low, and there will be no slipping phenomenon due to the precipitation of the free silane coupling agent. In the present invention, POE has no special restrictions and can be directly obtained from the market, such as 8450, 8150, 8440 of Dow, DF810, DF610, DF710 of Mitsui Chemicals, etc.; POP also has no special restrictions and can be directly obtained from the market, such as 1840G of Trinseo, Supreme021 of SK of South Korea, GA1875 of Dow, etc.

[0028] For example, the grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer can be any value among 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, etc. or any value therebetween, without any particular limitation. For example, the weight content of the free silane coupling agent in the silane coupling agent grafted polyolefin elastomer can be any value among 0.2wt%, 0.18wt%, 0.15wt%, 0.12wt%, 0.1wt%, 0.08wt%, 0.06wt%, 0.05wt%, etc. or any value therebetween, without any particular limitation. In the present invention, the method for detecting the weight content of free silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not limited, for example, the following method can be used: 0.01-0.1g of silane coupling agent grafted polyolefin elastomer particles are taken and pressed into a film with a thickness of about 0.05-0.15mm, and the film is immersed in alcohol for 10-30min, and the alcohol on the surface of the film is removed and wiped off, and the infrared absorbance of the film before and after immersion in alcohol is tested to calculate the weight content of the free silane coupling agent.

[0029] In a preferred embodiment of the present invention, the weight proportion of the silane coupling agent grafted polyolefin elastomer in the packaging film is not less than 90%. The silane coupling agent grafted polyolefin elastomer is the main material of the packaging film. An insufficient weight proportion in the packaging film will affect the performance of the packaging film. For example, the weight proportion of the silane coupling agent grafted polyolefin elastomer in the packaging film can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, etc., or any value in between, without special restrictions.

[0030] In a preferred embodiment of the present invention, the silane coupling agent is a silane coupling agent having a carbon-carbon double bond at the end group. The carbon-carbon double bond at the end group reacts with the polyolefin elastomer under the presence of a free radical initiator and the silane coupling agent is grafted onto the polyolefin elastomer.

[0031] In a more preferred embodiment of the present invention, the general formula of the silane coupling agent is as shown in the following formula (1):

[0032] CH2=C(R 1 )R 2 S i 3 a (OR 4 ) b (1)

[0033] Among them, R 1is selected from H or C1-C4 alkyl, R 2 is absent, C1-C8 alkylene or C2-C10 substituted alkylene, R 3 and R 4 Independently selected from C1-C4 alkyl, 0≤a≤1, a+b=3. For example, the silane coupling agent of the present invention can be any one of vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, allyloxytrimethoxysilane, allyloxytriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltriethoxysilane, acryloxypropyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, etc., or a combination of two or more thereof.

[0034] In a preferred embodiment of the present invention, the grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not less than 4wt%. Within a certain range of the grafting rate of the silane coupling agent, the higher the grafting rate of the silane coupling agent, the higher the polarity of the silane coupling agent grafted polyolefin elastomer, and the higher the bonding strength. For example, the grafting rate of the silane coupling agent can be any value among 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, etc. or any value therebetween, without any particular limitation.

[0035] In a preferred embodiment of the present invention, the grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not higher than 10wt%. Since the silane coupling agent is easily hydrolyzed and condensed in a humid environment, if the grafting rate of the silane coupling agent is too high, it is not conducive to the stability and performance of the encapsulation film product. More preferably, the grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not higher than 8wt%. For example, the grafting rate of the silane coupling agent can be any value among 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, etc. or any value in between, without special restrictions.

[0036] In a preferred embodiment of the present invention, the silane coupling agent grafted polyolefin elastomer is prepared by a melt grafting method. The silane coupling agent grafted polyolefin elastomer is prepared by a melt grafting method, and the carbon-carbon double bond on the silane coupling agent is utilized, and under the action of an initiator, the silane coupling agent is grafted onto POE. The initiator of the above-mentioned melt grafting is not particularly limited, and can be a peroxide initiator, such as benzoyl peroxide, dodecyl peroxide, diisopropyl hydroperoxide, diisopropyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, tert-butyl peroxybenzoate, tert-butyl peroxypivalate, di-tert-butyl peroxide, cumene hydroperoxide, etc.

[0037] In a more preferred embodiment of the present invention, the melt grafting adopts a screw extruder, the melting section temperature is 80-200° C., and the die temperature is 150-200° C. Further, the screw extruder is a twin-screw extruder, which has better melting effect, higher mixing and extrusion efficiency, and is more conducive to the grafting reaction.

[0038] In a preferred embodiment of the present invention, the raw material components also include one or two or more combinations of crosslinking agent, auxiliary crosslinking agent, antioxidant, light stabilizer and ultraviolet light absorber. In the present invention, the crosslinking agent is an initiator, especially a peroxide initiator, as described above, and the amount can be 0.1-1% of the raw material component weight. The auxiliary crosslinking agent can be triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane diallyl ether, triallyl cyanurate, trimethylallyl isocyanate, ethylene glycol dimethacrylate, diethylene glycol divinyl ether, etc., and the amount can be 0.5-3% of the raw material component weight. Antioxidants (such as antioxidant 1010, antioxidant 168), light stabilizers (such as 127UV, 527UV, etc.) and ultraviolet light absorbers (such as UV284, UV326, UV328, etc.) can all be directly purchased from the market, and the amount can be 0.1-1% of the raw material component weight.

[0039] The technical solution of the present invention is further described and illustrated according to various embodiments below. Unless otherwise specified, the parts described in the following embodiments are parts by weight.

[0040] Example 1

[0041] Take 97 parts of POE (Dow 8450), 3.7 parts of vinyltrimethoxysilane and 0.3 parts of diisopropylbenzene hydroperoxide, add them to a mixer and mix them evenly at 90°C, then transfer them to a twin-screw extruder for melt grafting and granulation. The melting section temperature is 130-200°C and the die temperature is 170-180°C to obtain silane coupling agent grafted POE. The grafting rate is measured to be 3.1wt%, and the weight content of free vinyltrimethoxysilane is 0.12wt%.

[0042] It is possible that a small amount of vinyltrimethoxysilane volatilizes during the mixing and melting process. Therefore, when the weight content of free vinyltrimethoxysilane is very low, the grafting rate (3.1wt%) is lower than the feed ratio of vinyltrimethoxysilane (3.66wt%).

[0043] The test method of the grafting rate is: first use ICP-OES to test the content of Si atoms in the grafted POE with a known silane coupling agent grafting rate, and then use FT-IR to test the absorbance of the silane characteristic absorption peak in the POE grafted with a known silane coupling agent to obtain the correction coefficient of FT-IR detection. Then use FT-IR to detect the absorbance of the silane characteristic absorption peak in the POE grafted with a silane coupling agent obtained above, multiply it by the correction coefficient, and the grafting rate of the silane coupling agent is measured.

[0044] The test method for free silane coupling agent is as follows: take 0.01g of the above silane coupling agent grafted POE particles and press them into a film with a thickness of about 0.1mm, soak them in alcohol for 10min, take them out and wipe off the alcohol on the surface of the film, and test the infrared absorbance of the film before and after soaking in alcohol. Figure 1 The weight content of the free silane coupling agent was calculated by comparing the peak areas of the absorbance of the peak at position a (silane absorption peak) shown in FIG. Figure 1 In the figure, A is the absorbance spectrum of the film before immersion, and B is the absorbance spectrum of the film after immersion. It can be found that spectrum A and spectrum B are basically overlapped, indicating that the weight content of free vinyltrimethoxysilane in the silane coupling agent grafted POE obtained in this embodiment is low, and the actual measured value is only 0.12wt%.

[0045] Example 2

[0046] Take 96 parts of POE (Dow 8450), 4.5 parts of vinyltrimethoxysilane and 0.3 parts of diisopropylbenzene hydroperoxide, add them to a mixer and mix them evenly at 90°C, then transfer them to a twin-screw extruder for melt grafting and granulation. The melting section temperature is 130-200°C and the die temperature is 170-180°C to obtain silane coupling agent grafted POE. The grafting rate is measured to be 4.1wt%, and the weight content of free vinyltrimethoxysilane is 0.17wt%.

[0047] Example 3

[0048] Take 91.5 parts of POE (Dow 8450), 8.7 parts of vinyltrimethoxysilane and 0.5 parts of diisopropylbenzene hydroperoxide, add them to a mixer and mix them evenly at 90°C, then transfer them to a twin-screw extruder for melt grafting and granulation. The melting section temperature is 130-200°C and the die temperature is 170-180°C to obtain silane coupling agent grafted POE. The grafting rate is measured to be 7.9wt%, and the weight content of free vinyltrimethoxysilane is 0.10wt%.

[0049] Example 4

[0050] Take 90 parts of POE (Dow 8450), 10.5 parts of vinyltrimethoxysilane and 0.5 parts of diisopropylbenzene hydroperoxide, add them to a mixer and mix them evenly at 90°C, then transfer them to a twin-screw extruder for melt grafting and granulation. The melting section temperature is 130-200°C and the die temperature is 170-180°C to obtain silane coupling agent grafted POE. The grafting rate is measured to be 9.8wt%, and the weight content of free vinyltrimethoxysilane is 0.14wt%.

[0051] Comparative Example 1

[0052] Take 99 parts of POE (Dow 8450), 1.3 parts of vinyltrimethoxysilane and 0.3 parts of diisopropylbenzene hydroperoxide, add them to a mixer and mix them evenly at 90°C, then transfer them to a twin-screw extruder for melt grafting and granulation. The melting section temperature is 130-200°C and the die temperature is 170-180°C to obtain silane coupling agent grafted POE. The grafting rate is measured to be 1.1wt%, and the weight content of free vinyltrimethoxysilane is 0.08wt%.

[0053] Comparative Example 2

[0054] The difference between this comparative example and comparative example 1 is that in comparative example 1, the amount of vinyl trimethoxy silane is adjusted from 1.3 parts to 2.8 parts. The other steps remain unchanged. Silane coupling agent grafted POE is obtained, and the grafting rate is measured to be 2.3wt%, and the weight content of free vinyl trimethoxy silane is 0.17wt%.

[0055] Example 5

[0056] Take 70 parts of POE (Dow 8150), 26 parts of POP (Dow GA1875), 5.8 parts of vinyltrimethoxysilane and 0.4 parts of di-tert-butyl peroxide, add them into a mixer and mix them evenly at 90°C, then transfer them to a twin-screw extruder for melt grafting and granulation. The melting section temperature is 130-200°C and the die temperature is 170-180°C to obtain a silane coupling agent grafted polyolefin elastomer. The grafting rate is measured to be 5.1wt%, and the weight content of free vinyltrimethoxysilane is 0.12wt%.

[0057] Example 6

[0058] The difference between this embodiment and embodiment 5 is that in embodiment 5, vinyl trimethoxysilane is replaced by an equal weight of γ-methacryloxypropyl trimethoxysilane. The remaining steps remain unchanged to obtain a silane coupling agent grafted polyolefin elastomer, and the grafting rate is measured to be 5.4wt%, and the weight content of free γ-methacryloxypropyl trimethoxysilane is 0.07wt%.

[0059] Example 7

[0060] The difference between this embodiment and embodiment 6 is that in embodiment 6, the amount of γ-methacryloxypropyltrimethoxysilane is adjusted from 5.8 parts to 7.5 parts. The remaining steps remain unchanged to obtain a silane coupling agent grafted polyolefin elastomer, and the grafting rate is measured to be 7.3wt%, and the weight content of free γ-methacryloxypropyltrimethoxysilane is 0.09wt%.

[0061] Example 8

[0062] The difference between this embodiment and embodiment 6 is that in embodiment 6, the amount of γ-methacryloxypropyltrimethoxysilane is adjusted from 5.8 parts to 9.0 parts. The remaining steps remain unchanged to obtain a silane coupling agent grafted polyolefin elastomer, and the grafting rate is measured to be 8.7wt%, and the weight content of free γ-methacryloxypropyltrimethoxysilane is 0.13wt%.

[0063] Performance Testing

[0064] The encapsulation film is obtained by the following steps according to the following raw material components: mixing, plasticizing and extruding, roller casting, pulling, winding and cutting.

[0065] Raw material components: 96.9 parts of silane coupling agent grafted POE (or silane coupling agent grafted polyolefin elastomer), 2 parts of auxiliary cross-linking agent trimethylolpropane trimethacrylate, 0.5 parts of antioxidant 1010, 0.3 parts of light stabilizer 127UV and 0.3 parts of ultraviolet absorber UV284.

[0066] Peel strength: Test the peel strength of the encapsulation film to the glass substrate in accordance with ASTM D903-98. And test the peel strength retention rate after moisture and heat aging.

[0067] Damp heat aging test conditions: Test conditions, 85℃, relative humidity 85%, test time is 1000h and 2000h respectively.

[0068] UV aging yellowing index: at 60kW·h / m 2 The UV aging yellowing test is carried out under UV light intensity conditions in accordance with GB / T 29848-2018.

[0069] The results are shown in Table 1 below.

[0070] Table 1

[0071]

[0072] Combining the results of the above embodiments and the results of Table 1, it can be seen that the packaging film of the present invention has a higher silane coupling agent grafting rate, and the free silane coupling agent content in the grafted polyolefin elastomer after melt grafting is very low. The packaging film has good bonding strength to the glass substrate and good aging resistance. Even after a long period of aging, it can still maintain a high bonding strength, which can avoid or solve the problem of film slippage.

[0073] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

Claims

1. A perovskite photovoltaic cell encapsulation film, characterized in that: The raw material components include a silane coupling agent grafted polyolefin elastomer; The grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not less than 3wt%, and the weight content of the free silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not higher than 0.2wt%.

2. The perovskite photovoltaic cell encapsulation film according to claim 1, characterized in that: The weight proportion of the silane coupling agent grafted polyolefin elastomer in the packaging film is not less than 90%.

3. The perovskite photovoltaic cell encapsulation film according to claim 1, characterized in that: The silane coupling agent is a silane coupling agent having a carbon-carbon double bond at the end group.

4. The perovskite photovoltaic cell encapsulation film according to claim 3, characterized in that: The general formula of the silane coupling agent is shown in the following formula (1): CH2=C(R 1 )R 2 SiR 3 a (OR 4 ) b (1) Among them, R 1 is selected from H or C1-C4 alkyl, R 2 is absent, C1-C8 alkylene or C2-C10 substituted alkylene, R 3 and R 4 Independently selected from C1-C4 alkyl, 0≤a≤1, a+b=3.

5. The perovskite photovoltaic cell encapsulation film according to claim 1, characterized in that: The grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not less than 4wt%.

6. The perovskite photovoltaic cell encapsulation film according to claim 1, characterized in that: The grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not higher than 10wt%.

7. The perovskite photovoltaic cell encapsulation film according to claim 6, characterized in that: The grafting rate of the silane coupling agent in the silane coupling agent grafted polyolefin elastomer is not higher than 8wt%.

8. The perovskite photovoltaic cell encapsulation film according to claim 1, characterized in that: The silane coupling agent grafted polyolefin elastomer is prepared by a melt grafting method.

9. The perovskite photovoltaic cell encapsulation film according to claim 8, characterized in that: The melt grafting adopts a screw extruder, the melting section temperature is 80-200°C, and the die temperature is 150-200°C.

10. The perovskite photovoltaic cell encapsulation film according to claim 1, characterized in that: The raw material components further include one or a combination of two or more of a crosslinking agent, a co-crosslinking agent, an antioxidant, a light stabilizer and an ultraviolet absorber.

Citation Information

Cited By

  • Graft copolymer resin for packaging adhesive film, packaging adhesive film as well as preparation method and application of graft copolymer resin

    CN121181783A